Spin-on-Glass (SOG) based insulator of stack coupled microcoils for MEMS sensors and actuators application - Jumril Yunas,; Burhanuddin Yeop Majlis,; Azrul Azlan Hamzah,; Badariah Bais, (Universiti Kebangsaan Malaysia, 2014)
A comprehensive study on the SOG (Spin-on-Glass) based thin film insulating layer is presented. The SOG layer has been fabricated using simple MEMS technology which can play an important role as insulating layer of stack coupled microcoils. The fabrication process utilizes a simple, cost effective process technique as well as CMOS compatible resulting to a reproducible and good controlled process. It was observed that the spin speed and material preparation prior to the process affect to the thickness and surface quality of the layer. Through the annealing process at temperature 425oC in N2 atmospheric for 1 h, a 750 nm thin SOG layer with the surface roughness or the uniformity of about 1.5% can be achieved. Furthermore, the basic characteristics of the spiral coils, including the coupling characteristics and its parasitic capacitance were discussed in wide range of operating frequency. The results from this investigation showed a good prospect for the development of fully integrated planar magnetic field coupler and generator for sensing and actuating purposes.